Description of domestic accidents during childhood: DOI: 10.15343/0104-7809.2013374394400 - Mourão Xavier-Gomes, Ludmila (2013)
The childhood home accidents are an important source of concern, as they are growing causes of mortality and disabilityin Brazil. The aim of this study was to identify and describe childhood home accidents of a Health Community Agent Strategy(EACS) in Montes Claros, Minas Gerais, Brazil. This is a descriptive, retrospective, quantitative study accomplishedthrough a structured questionnaire applied with parents or guardians of children aged between zero and 12 years in thehome environment. The study included fifty parents or guardians. One hundred and four household accidents were recorded.Nineteen children (38.0%) were male and 31 (62.0%) were female. Regarding age, six accidents (12.0%) occurredamong children aged from three to eight months, 15 accidents (30.0%) involved children from eight months to less thanfour-years, 11 accidents (22.0%) occurred in children from four to less than eight years and 18 accidents (36.0%) occurredwith children from eight to 12 years. The study shows that the parents’ presence does not prevent accidents from occurring,since in 97 (93.3%) accidents the children were accompanied by the parents. The types of accidents registered wereelectric shock, impact, cuts, slips, poisoning, airway obstruction, fall and burn. Among these, falls were the most common.It was concluded that children are very vulnerable to accidents and that the home environment may involve risks or safety.